2022
DOI: 10.1002/ana.26436
|View full text |Cite
|
Sign up to set email alerts
|

GGC Repeat Expansion of RILPL1 is Associated with Oculopharyngodistal Myopathy

Abstract: Objective Oculopharyngodistal myopathy (OPDM) is an adult‐onset neuromuscular disease characterized by progressive ptosis, dysarthria, ophthalmoplegia, and distal muscle weakness. Recent studies revealed that GGC repeat expansions in 5′‐UTR of LRP12, GIPC1, and NOTCH2NLC are associated with OPDM. Despite these advances, approximately 30% of OPDM patients remain genetically undiagnosed. Herein, we aim to investigate the genetic basis for undiagnosed OPDM patients in two unrelated Chinese Han families. Methods P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 49 publications
(132 reference statements)
1
28
0
Order By: Relevance
“…A dot-like sarcoplasmic deposition of p62 and small angular fibers are also common. [7][8][9][11][12][13] Ultrastructural studies have shown tubulofilamentous intranuclear inclusions of 17.3 nm in diameter in 1 OPDM1 patient, which are larger than those observed in oculopharyngeal muscular dystrophy (OPMD) or OPDM3. 9,13 In this issue of Muscle & Nerve, Shimizu and colleagues report seven Japanese patients from five families with OPDM1.…”
mentioning
confidence: 92%
See 2 more Smart Citations
“…A dot-like sarcoplasmic deposition of p62 and small angular fibers are also common. [7][8][9][11][12][13] Ultrastructural studies have shown tubulofilamentous intranuclear inclusions of 17.3 nm in diameter in 1 OPDM1 patient, which are larger than those observed in oculopharyngeal muscular dystrophy (OPMD) or OPDM3. 9,13 In this issue of Muscle & Nerve, Shimizu and colleagues report seven Japanese patients from five families with OPDM1.…”
mentioning
confidence: 92%
“…To date, the expansion of CGG repeats in the 5 0 untranslated region (5 0 UTR) of LRP12 (OPDM1), GIPC1 (OPDM2), NOTCH2NLC (OPDM3), and RILPL1 (OPDM4) have been reported to cause OPDM in Japan and China. [6][7][8][9][10][11][12][13] Among these 4 OPDM subtypes, OPDM1 is the most common OPDM subtype in Japan, accounting for 31.25% of Japanese OPDM patients, while OPDM2 is the most common OPDM subtype in China, accounting for 37.3% of Chinese OPDM…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Repeat expansion diseases are caused by unstable expanded tri-, tetra-, penta-, hexa- or dodecanucleotides that can be located in coding or noncoding gene regions, namely 5′-untranslated regions (UTR), 3′-UTR, introns, or promoters ( Figure 1 ) [ 1 ]. In recent years, a new group of five trinucleotide repeat expansion diseases has been reported, including neuronal intranuclear inclusion disease (NIID) [ 4 , 5 ], oculopharyngeal myopathy with leukoencephalopathy 1 (OPML1) [ 4 ], and oculopharyngodistal myopathies 1–4 (OPDM1–4) [ 4 , 6 , 7 , 8 , 9 ]. Beyond the simple STR expansions, pentanucleotide pathological insertions have also been identified, with the first being the (TGGAA) n in SCA31 [ 10 ] and later the (ATTTC) n in SCA37 [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Many of the known repeat expansions are transcribed bidirectionally from both DNA strands [ 18 ]. More recently, bidirectional transcription has been reported for OPML1-associated gene LOC642361/NUTM2B-AS1 [ 4 ] and RILPL1 in OPDM4 [ 9 ]. The vast diversity of genes containing disease-causing repeat expansions, combined with the rapid increase in the number of pathogenic STRs that have been discovered in the last years, highlights the need for studying the molecular mechanisms triggered by these mutations.…”
Section: Introductionmentioning
confidence: 99%